2012
DOI: 10.4097/kjae.2012.62.6.552
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lidocaine and procaine on microRNA expression of adipocyte-derived adult stem cells

Abstract: BackgroundThe microRNA (miRNA) pathway has emerged as one of the biologic pathways implicated in stem cell regulation. miRNA is a noncoding, single-stranded RNA consisting of 20-25 nucleotides that inhibits the protein production at the step of translation. The molecular effects of lidocaine and procaine on adipose stem cells were investigated by examining RNA expression array.MethodsAdipose stem cells were isolated from a prior abdominal liposuction procedure. The human adipose stem cells were cultured and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(37 reference statements)
0
11
0
1
Order By: Relevance
“…Sung and coworkers investigated the relationship between MSCs and expression levels of microRNAs (miRNAs) using peptide nucleic acid (PNA)‐miRNA array analysis. This study demonstrated that lidocaine treatment of MSCs affects miRNA expression and that the effect of procaine is more significant than the one of lidocaine . The effects of lidocaine on human MSC functions have been addressed previously, but there were no studies examining their recovery following exposure .…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Sung and coworkers investigated the relationship between MSCs and expression levels of microRNAs (miRNAs) using peptide nucleic acid (PNA)‐miRNA array analysis. This study demonstrated that lidocaine treatment of MSCs affects miRNA expression and that the effect of procaine is more significant than the one of lidocaine . The effects of lidocaine on human MSC functions have been addressed previously, but there were no studies examining their recovery following exposure .…”
Section: Discussionmentioning
confidence: 77%
“…The cytotoxicity of amide‐type local anesthetics including bupivacaine, ropivacaine, mepivacaine, and lidocaine to MSCs in both human and animal models has been reported in previous studies . However, only a few investigators have reported deleterious cytotoxic effects of varying concentrations of local anesthetics on MSCs after different exposure and assessment times . Sung and coworkers investigated the relationship between MSCs and expression levels of microRNAs (miRNAs) using peptide nucleic acid (PNA)‐miRNA array analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por otra parte Harato et al (2012) establecen que bupivacaína induce apoptosis en la línea celular Neuro2a por medio de síntesis de sustancias reactivas del oxígeno (ROS) y activación de p38 MAPK. A su vez ha sido observada la citotoxicidad de lidocaína (Jacobs et al, 2011) y procaína (Park et al, 2011) en células cartilaginosas; y de bupivacaína en células madres adiposas (Sung et al, 2012).…”
Section: Autor Técnica Anestésica Estudiadaunclassified